Treatment-Associated Neuroplastic Changes in People with Stroke-Associated Ataxia—An fMRI Study - Patricia Meier; Christian Siedentopf; Lukas Mayer-Suess; Michael Knoflach; Stefan Kiechl; Gudrun Sylvest Schönherr; Astrid E. Grams; Elke R. Gizewski; Claudia Lamina; Malik Galijasevic; Ruth Steiger (Neurology International, 2025)
Background/Objectives: In consideration of the significance of the pursuit of training-induced neuroplastic changes in the stroke population, who are reliant on neurorehabilitation treatment for the restoration of neuronal function, the objectives of this trial were to investigate fMRI paradigms for acute stroke patients with ataxic symptoms, to follow up on changes in motor function and balance due to recovery and rehabilitation, and to investigate the different effects of two treatment methods on neuronal plasticity. Methods: Therefore, fMRI-paradigms foot tapping and the motor imagery (MI) of a balancing task (tandem walking) were employed. Results: The paradigms investigated were suitable for ataxic stroke patients to monitor changes in neuroplasticity while revealing increased activity in the primary motor cortex (M1) and the cerebellum over 3 months of treatment. Furthermore, analysis of the more complex balance task revealed augmented activation of association areas due to training. Coordination exercises, constituting a specific treatment of ataxic symptoms, indicate more consolidated brain activations, corresponding to a faster motor learning process. Activation within Brodmann Area 7 has been prominent among all paradigms, indicating a special importance of this region for coordinative functions. Conclusions: Further studies are needed to confirm our results in larger patient groups. Clinical Trial Registration: German Clinical Trials Registry (drks.de). Identifier: DRKS00020825. Registered 16.07.2020.